KONTRIBUSI MOTIVASI BERPRESTASI TERHADAP PRESTASI AKADEMIK SISWA KELAS XI SMA NEGERI 10 SEMARANG - Sugiyanto Sugiyanto (Paradigma, 2009)
This research applied toward 197 XI grade SMA Negeri 10 Semarang students. To collect the data, researcher used both questionnaire and the student documents. This research is aimed to know the significance of contribution achievement motivation toward achievement academic (cognitive aspect, affective aspect, and psychomotor aspect). Collected data was analyzed by product moment correlation and the regresion analysis. The final result of correlation analysis show that there is a positive contribution achievement motivation toward achievement academic (cognitive 0,7396, affective 0,4225, psychomotor 0,4096). Based on this research result, it suggests that achievement motivation term can be used as one variable contributed toward academic achievement to the next research.Keywords : Achievement Motivation, Achievement Academic.